Web-based psychoeducational interventions for managing cognitive impairment–a systematic review - Vuori, Outi; Kallio, Eeva-Liisa; Wikström, Annamaria; Jokinen, Hanna; Hietanen, Marja (Frontiers in Neurology, 2023)
Objective Web-based rehabilitation, a branch of telerehabilitation, is carried out over the internet, unrestricted by time or place. Even though web-based interventions have been reported as feasible and effective in cases of mood disorders, for example, such evidence on the effectiveness of web-based cognitive rehabilitation remains unclear. This systematic review summarizes current knowledge on web-based psychoeducational programs aiming to manage cognitive deficits in patients with diseases that affect cognition. Methods Using the Ovid database and the Web of Science, we systematically searched the Cochrane Database of Systematic Reviews, Medline, and PsycINFO to identify eligible studies. The review protocol (CRD42021257315) was pre-registered with the PROSPERO International Prospective Register of Systematic Reviews. The search was performed 10/13/2022. Two reviewers independently screened titles, abstracts, and full-texts, and extracted data for the selected studies. Two independent reviewers assessed the methodological quality. Results The search retrieved 6,487 articles. Four studies with different patient groups (stroke, traumatic brain injury, brain tumor, and cancer) met the inclusion criteria of this systematic review. The studies examined systematic cognition-focused psychoeducational rehabilitation programs in which the patient worked independently. Three studies found positive effects on subjective cognitive functions, executive functions, and self-reported memory. No effects were found on objective cognitive functions. However, the studies had methodological weaknesses (non-randomized designs, small sample sizes, vaguely described interventions). Overall, adherence and patient satisfaction were good/excellent. Conclusion Web-based cognitive intervention programs are a new approach to rehabilitation and patient education. The evidence, although scarce, shows that web-based interventions are feasible and support subjective cognitive functioning. However, the literature to date is extremely limited and the quality of the studies is weak. More research with high-quality study designs is needed. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=257315, identifier: CRD42021257315.